Performance analysis of Reverse and Frugal Innovations in Nigeria A Case Study of IVM automobile company - Chipanje, Bridget; Ying, Dong; Haiping, Lv (Technium Social Sciences Journal, 2021)
Nigeria which is considered as the ‘giant’ of Africa and is currently the largest economy in West Africa is also fast becoming the largest economy in the entire Africa. The country is in the process of developing a broader base for her economy which for many years has been reliant on oil and gas and non-renewable fossil fuels which are already saturated. However, the country has many other natural resources, and one of the major companies in the “non-oil” economy is the Innoson Vehicles and Motors (IVM) in Nigeria. In recent decades, many West African companies, including IVM, have begun to accept the need for innovation if they are to sell their products to a wider market and to increase exports. Noteworthy to companies in West Africa are Reverse Innovation and Frugal Innovation. This research observes the interaction these two forms of innovation adopts, innovation, and the ways in which they have been accepted by the IVM and their supply chain. There are three stages of management considered in this research (Macro; Directors and Educational Advisors Managers, members of this level precipitate policies that advance the economy and business inside the company. Meso; Senior Management at the production unit in the IVM, and Micro; The Organizational Supervisors of manufacturing and distribution). To achieve the purpose of this research, several personnel’s at the three different levels of management were interviewed about their understanding of the terms and the application of Reverse and Frugal innovations in their experience. A total of 20 interviews (each lasting 15-20 minutes) were carried out, 8 at the Macro level, 5 Meso level and 7 at the Micro level. This led to a discovery that West African businesses found Reverse Innovation and Frugal very satisfactory, and inherent, should it be that the economic proliferation designed is continued. The study, by analyzing their opinions concerning the drivers and limitations of Reverse Innovation and Frugal Innovation, has successfully generated a framework for R&F innovations which establishments in other developing economies seeking to proliferate their exports back to the developed countries might find beneficial. Finally, sustainability is also seen as an underlying influencing factor throughout the research.